Use of oat fiber with different particle size in baking: rheological and textural effect - Cordero Fernández, Diana Laura; Granados Nevárez, María del Carmen; Islas Rubio, Alma Rosa; Verdú Amat, Samuel; Ramírez-Wong, Benjamín; Vasquez Lara, Francisco (Revista Mexicana de Ciencias Agrícolas, 2020)
The objective of this work was to evaluate the effect of replacing wheat flour (HT) with oat fiber flour (HFA) with different particle size on the rheological, textural and baking properties. The particle size obtained after grinding oat fiber was 250 and 177 µm (microns). The replacement percentages used were 10, 20 or 30%. Flour mixtures were determined color, water retention capacity (CRA) and viscosity profile. The dough was measured for strength and extensibility by the Kieffer test, while the bread was measured for specific volume, water activity and texture profile. The results showed increases in force in the dough when the two fractions of HFA (250 or 177 µm) were used in the substitution of HT with respect to that obtained from HT (0.25 N). In extensibility, the most important increases were observed when 177 µm HFA was used. The specific bread volume was favored when 10 or 20% of HFA (177 µm) was used, observing very similar values between them (4.54 and 4.56 cm3 g-1, respectively), without showing significant differences to that obtained from HT (4.57 cm3 g-1). The texture profile showed the obtaining of softer breads when HFA (177 µm) was used, in its three different replacement percentages (4.86, 4.71 and 7.05 N), even improved as measured in HT (7.84 N).